Konsep Sastera Islam mengikut Nasr el-Din Ibrahim Ahmed Hussein = The concept of Islamic Literature by Nasr el-Din Ibrahim Ahmed Hussein - Yaacob, Adli (Global Academic Excellence (M) Sdn Bhd (GAE), 2022)
This study discusses the concept of Islamic literature organized by Nasr El-din Ibrahim Ahmed Hussein. The strength of the concept brought by Nasr El-din is to focus on the "Islamization of knowledge", especially in the field of Arabic literature, in line with his career as a scholar who highly emphasizes the Islamic values in every teaching and learning process. He strongly emphasized the link between Islamic literature and tauhid as the core of his concept. He believes that the good literary work begins from a pure (inner) soul, thus, the soul becomes clean as it is decorated with true and prosperous faith. Literary is a medium to describe the natural feelings experienced by human beings. Religion will direct a person’s literary work in the scope of goodness in order to achieve the purpose of God. Therefore, the elements of the aqidah and the literature are interconnected. This study generally examines and refines his criticisms and views as a guide to enhancing the value to the current Islamic literature in order to be understood in line with the purity of their goals.